Psychological morbidity associated with ovarian cancer screening: results from more than 23 000 women in the randomised trial of ovarian cancer screening (UKCTOCS). (28th May 2014) - Barrett, J; Jenkins, V; Farewell, V; Menon, U; Jacobs, I; Kilkerr, J; Ryan, A; Langridge, C; Fallowfield, L; UKCTOCS trialists
<x xml:space="preserve">Abstract</x> Objective To examine the psychological sequelae associated with abnormal screening in the United Kingdom Collaborative Trial of Ovarian Cancer Screening (UKCTOCS). Design Prospective, longitudinal randomised control trial. Setting Sixteen UKCTOCS centres. Sample Women aged 50–70 years randomised to annual multimodal screening, ultrasound screening or control groups. Methods Two groups were followed for 7 years: (1) a random sample (n = 1339), taken from all three study groups; and (2) an events sample (n = 22 035) of women with abnormal screens resulting in the need for repeat testing of either low or higher level intensity. Main outcome measures Patient‐reported measures of anxiety (scores ranging from 20 to 80) and psychological morbidity. Results In the random sample the mean difference between anxiety scores after a repeat screening and those following an annual screening was 0.4 (95% CI −0.46, 1.27), and in the events sample it was 0.37 (95% CI 0.23, 0.51). The risk of psychological morbidity was only increased in the event sample for women requiring higher level repeat screening (OR 1.28; 95% CI 1.18, 1.39). The risk of psychological morbidity in women with ovarian cancer was higher at both 6 weeks (OR 16.2; 95% CI 9.19, 28.54) and 6 months (OR 3.32; 95% CI 1.91, 5.77) following surgery. Conclusions Screening does not appear to raise anxiety but psychological morbidity is elevated by more intense repeat testing following abnormal annual screens, and in women after surgical treatment for ovarian cancer.